Entomofauna asociada al cultivo de espárragos en el departamento del Cauca, Colombia - Caicedo, AM; Bellotti, Anthony C. (2002)
The principal entomological problems that affect asparagus production in Cauca State were determined and those arthropods that could be present in the marketable product were identified. The study was carried out on three farms, two of them located in the municipality of Cajibío and the third in Totoró. Average altitudes was 1800-1840 m.a.s.l. and on average temperature of 15°C, RH 83-86%. Asparagus plots were separated according to their development stage, with the sample area of three hectares, and five ramdon samples with a sweep-net as well as direct observations of adults and immatures. The samples were taken every two weeks. 1.440 Individuals were collected and 70 species were selected according to their number and presence during the crop cycle. 46 species from 10 orders and 20 families were identified. The most economically, important and abundant orders were Hemiptera, Coleoptera, Lepidoptera, Homoptera y Thysanoptera. The Lepidoptera species Paracles severa (Berg.), Copitarsia consueta (Walker) y Spodoptera sp. nr marima (Schaus) were the first register for these species on asparagus in Colombia. Also recorded was the aphid, Myzus persicae (Sulzer), considered of great importance as it transmits 120 virus diseases. The thysanopteran Thrips tabaci Lindeman was also found throughout the crop cycle, including the harvested product. In addition several beneficial species were collected from the orders, Hymenoptera, Neuroptera, Diptera y Coleoptera, including Pantomona testacea Klung, Homolobus sp., Campsomeris dorsata (F.), Chrysoperla externa (Hagen). parasiting and predating pest species. Plant species used as ground cover in asparagus plantations were also identified for the three farms.